Resilience to hydrological droughts in the northern Murray-Darling Basin, Australia. (12th December 2022) - Quentin Grafton, R.; Chu, Long; Kingsford, Richard T.; Bino, Gilad; Williams, John
Abstract : We respond to the problem of declining streamflows in the northern Murray–Darling Basin, Australia, a region that suffers from hydrological droughts and a drying trend. We partitioned the effect of meteorological trends from anthropogenic drivers on annual streamflow, quantified the effect of annual streamflow decline on waterbird abundance, estimated the effects of streamflow change on a measure of ecosystem resilience, and calculated the net benefits of in-stream water reallocation. The anthropogenic drivers of hydrological droughts were assessed by comparing the Lower Darling (hereafter the Barka) River, which has large recorded water extractions, with the adjacent Paroo River, which has very little recorded water extractions. Findings include: (1) only about one-third of the recent reduced streamflow of the Barka River is due to a meteorological drying trend; (2) statistically significant declines in waterbird species richness and abundance have occurred on both rivers between 1983–2000 and 2001–2020; (3) declines in waterbird abundance have been much larger along the Barka River than the Paroo River; and (4) ecosystem resilience, as measured by waterbird abundance, wasgreater on the Paroo River. Our four-step framework is applicable in any catchment with adequate time-series data and supports adaptive responses to hydrological droughts. This article is part of the Royal Society Science+ meeting issue 'Drought risk in the Anthropocene'.